2020
DOI: 10.3390/s20247094
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning-Based Joint User Pairing and Power Allocation in MIMO-NOMA Systems

Abstract: In this paper, we consider a multiple-input multiple-output (MIMO)—non-orthogonal multiple access (NOMA) system with reinforcement learning (RL). NOMA, which is a technique for increasing the spectrum efficiency, has been extensively studied in fifth-generation (5G) wireless communication systems. The application of MIMO to NOMA can result in an even higher spectral efficiency. Moreover, user pairing and power allocation problem are important techniques in NOMA. However, NOMA has a fundamental limitation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Simulation results demonstrated that the proposed DL-based solution was able to achieve a significant rate advantage with respect to other trivial approaches, such as fixed or random cluster assignments. In [104], the authors proposed an RL-based joint UP and power allocation scheme. By applying Q-learning, it is possible to perform UP and power allocation simultaneously, which was the key novelty of the presented work.…”
Section: Massive Mimo With Nomamentioning
confidence: 99%
“…Simulation results demonstrated that the proposed DL-based solution was able to achieve a significant rate advantage with respect to other trivial approaches, such as fixed or random cluster assignments. In [104], the authors proposed an RL-based joint UP and power allocation scheme. By applying Q-learning, it is possible to perform UP and power allocation simultaneously, which was the key novelty of the presented work.…”
Section: Massive Mimo With Nomamentioning
confidence: 99%
“…RL is a prominent strategy for dealing with the problem of uncertain and variable environments [ 24 ]. RL-based strategies for power allocation in an outage compensation situation were put forth in [ 25 , 26 ]. However, one disadvantage of RL-based techniques is that they may take a very long time to converge as they attempt to identify the best answer through the interaction of their environment via trial and error.…”
Section: Related Workmentioning
confidence: 99%
“…Different Game theory algorithms for multiple user pairing and machine learning algorithms for user pairing have been proposed in recent research. In [ 26 ], the authors proposed an RL-enabled joint power allocation and user pairing scheme. Through Q-learning, they were able to successfully implement both power allocation and user pairing with reduced computational complexity.…”
Section: Key Aspects For Practical Implementation Of Dl-based Nomamentioning
confidence: 99%
“…Lee J and So J. 24 proposed PA and user pairing based Reinforcement Learning (RL) using MIMO-NOMA. NOMA technique has the higher SE and widely used in 5G WC (Wireless Communication) systems.…”
Section: Related Workmentioning
confidence: 99%